(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
نفذ البحث خلال الموسمين الزراعيين 2016,2017 م في الساحل السوري في محافظة طرطوس قرية بيت الشيخ يونس لدراسة تأثير التسميد العضوي والكيميائي في بعض الصفات الإنتاجية (عدد النورات الزهرية/النبات, وزن الثمار/النبات غ , وزن الألف ثمرة غ, الإنتاجية من الثمار كغ/ه , دليل الحصاد%) لنبات الكزبرة (Coriandrum sativum L). استخدمت خمس معاملات سمادية المعاملة الأولى (T1) شاهد من دون تسميد، المعاملة الثانية (T2) تسميد كيميائي وفق المعادلة السمادية ] 80 NH4NO3(33%) ،120 P2O5(48%) ،60 K2O(50%)[ كغ/هـ،المعاملة الثالثة (T3) تسميد عضوي 20 طن/هـ،المعاملة الرابعة (T4) تسميد عضوي 30 طن/هـ، المعاملة الخامسة (T5) تسميد مختلط عضوي 15طن/هـ + كيميائي ]40 NH4NO3(33%) ،60 P2O5(48%) ،30 K2O(50%)[ كغ/هـ. صممت التجربة بطريقة القطاعات العشوائية الكاملة في ثلاثة مكررات ،سجلت معاملة التسميد الكيميائي زيادة في عدد النورات الزهرية/النبات, وزن الثمار/النبات غ , وزن الألف ثمرة غ, الإنتاجية من الثمار كغ/ه , دليل الحصاد%) مقارنة مع الشاهد خلال موسمي البحث. تفوق التسميد العضوي بالمعدل 30طن/ه (T4) على التسميد الكيميائي(T2) في جميع الصفات المشار إليها خلال موسمي البحث. أظهرت النتائج عدم وجود فروق معنوية بين المعاملة T4)) والمعاملة T5)) بالنسبة إلى معظم الصفات المدروسة. أعطى التسميد المختلط (T5) أعلى القيم في جميع الصفات المشار إليها وقدرت الإنتاجية من الثمار(730،880) كغ/ه على التوالي خلال موسمي البحث. The research was conducted during the agricultural seasons 2016,2017 m in the Syrian coast in Tartous governorate, the village of Beit Sheikh Yunus. To study the effect of organic and chemical fertilization on some productive traits (number of flower/plant, fruit weight /plant, weight of 1000 fruit gr, fruit yield Kg/h, harvest index%) of Coriander plant. Five fertilizer markers (first worker) were used,T1 was observed without fertilization ,The second treatment (T2) chemical fertilization according to the fertilizer [80 NH4NO3(33%) ،120 P2O5(48%) ،60 K2O(50%)] Kg/h, the third treatment (T3), organic fertilizer 20 Tons/h, treatment (T4) organic fertilizer 30 Ton/h ,treatment 5 (T5) mixed fertilizer(organic 15 Ton/h+chemical [40 NH4NO3(33%) ،60 P2O5(48%) ،30 K2O (50%)] Kg/h). The experiment was designed in a complete randomized manner in three replicates ,the treatment of chemical fertilization recorded an increase in the number of flowers/plants ,fruit weight /plants gr , weight of 1000 fruit gr, fruit yield Kg/h,harvest index %) compared to the control during the two research seasons. The organic fertilization rate at 30 T/ha (T4) exceeds the chemical fertilization (T2) in all the traits indicated during the two research seasons. The results showed no significant differences between treatment (T4) and treatment (T5) for must studied traits. Mixed fertilization gave the highest values in all the traits indicated and fruits production has been estimated with (730-880) Kg/h respectively during the two research seasons.